The Historical Foundations of the Narcotic Drug Control Regime - Buxton, Julia (World Bank, Washington, DC, 2012)
This paper outlines the institutional history of the international narcotic drug control regime. It details the evolution of the control system, from its foundations at the beginning of the twentieth century - a period of mass, unregulated narcotic drug use - to the current period. The paper argues that the contemporary control model is ill-positioned to address the dynamic and rapidly changing nature of the global narcotics trade. The persistence of anachronistic guiding first principles, specifically the utopian idea of prohibition, is identified as the key impediment to the adoption of a more humane and effective policy approach. But while there is growing pressure for a revision of founding ideas, this is not supported by a host of powerful actors that includes the United States.